SLEEP QUALITY OF POST-PARTUM MOTHERS WITH YOGA AND PILATES EXERCISE PROVISION: A COMPARATIVE STUDY - Anita Indra Afriani; Kumiyati Kumiyati; Dewi Mayangsari (Universitas Karya Husada Semarang, 2025)
Background: Role changes that occur during the postpartum period cause mothers to experience sleep disturbances because they have to wake up in the middle of the night to breastfeed their babies. Fatigue and changes in sleep patterns are one of the impressive things in the first year after a woman gives birth, which can have a negative effect on work, family life, and social relationships. One way to improve sleep quality is with yoga and pilates exercises. The purpose of this study was to determine the effectiveness of yoga and pilates exercises on the sleep quality of postpartum mothers at Welahan II Health Center. This research method was quantitative research, quasi-experimental design with two group pre and post test design, the study population was all postpartum mothers at Welahan II Health Center in March 2024. A sample of 10 yoga exercise respondents and 10 pilates exercise respondents. The results of this study There is effectiveness of yoga and pilates exercises on the sleep quality of postpartum mothers at Welahan II Health Center (p value 0.032 <0.05). The conclusion of the two interventions that is more effective on sleep quality is the provision of yoga exercise intervention.